Design of a Tool for Business Modeling of Cooperative Type in the Municipality of Pasto - Díaz Dávila, Juan Carlos; Delgado-Unigarro, Silvio; Martínez-Delgado, Diego (Cooperativismo & Desarrollo, 2022)
Faced with the difficulties facing the country and especially the municipality of Pasto as a result of the pandemic and the difficult situation of public order, in addition to the difficulties of access to financial resources and markets, alternative solutions are urgently required that reactivate development and capacities to generate stable sources of income and employment. The promotion of new companies and especially those of the cooperative type are especially relevant for their ability to generate self-employment, which depends to a large extent on adequate business modeling and structuring processes that lead to the formation of solid and lasting business organizations. In this article the preliminary results of the research are presented: Business modeling for cooperative companies in the municipality of pasto, whose main objective is to identify the appropriate way in which a cooperative-type enterprise, given its specificity and solidarity-based characteristics, It must advance the process of designing its business model and its correct implementation, to improve its chances of becoming a solid company with real possibilities of permanence and growth in its markets.